2016
DOI: 10.1038/srep23160
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting H5S2 phase in sulfur-hydrogen system under high-pressure

Abstract: Recently, hydrogen sulfide was experimentally found to show the high superconducting critical temperature (Tc) under high-pressure. The superconducting Tc shows 30–70 K in pressure range of 100–170 GPa (low-Tc phase) and increases to 203 K, which sets a record for the highest Tc in all materials, for the samples annealed by heating it to room temperature at pressures above 150 GPa (high-Tc phase). Here we present a solid H5S2 phase predicted as the low-Tc phase by the application of the genetic algorithm techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
58
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 27 publications
7
58
1
2
Order By: Relevance
“…Theoretically, many stoichiometries and crystal structures have been predicted for this phase, primarily based on analysis of thermodynamic stability. The proposed chemical compositions for this phase include H 2 S, HS 2 , H 4 S 3 , H 5 S 2 , and the “Magnéli” phases; some of them are only stable at high pressures. The T c values in these phases were calculated by different groups, using essentially the same methodology based on Eliashberg formulism.…”
Section: Superconductivity In Hydrogen Sulfidementioning
confidence: 99%
“…Theoretically, many stoichiometries and crystal structures have been predicted for this phase, primarily based on analysis of thermodynamic stability. The proposed chemical compositions for this phase include H 2 S, HS 2 , H 4 S 3 , H 5 S 2 , and the “Magnéli” phases; some of them are only stable at high pressures. The T c values in these phases were calculated by different groups, using essentially the same methodology based on Eliashberg formulism.…”
Section: Superconductivity In Hydrogen Sulfidementioning
confidence: 99%
“…Instead, first-principles calculations have provided insights for the superconducting phases. It is now established that some of the observed values of T c with the low-and high-T schemes are well reproduced [9][10][11][12][13][14][15][16][17] with crystal structures predicted for compositions of H 2 S [9], as well as H 5 S 2 [16] and H 3 S [10] (See Fig. 1).…”
mentioning
confidence: 93%
“…This result demonstrated that extreme pressures represent an avenue to access new physical phenomena and exotic states of matter, which in the next years may lead to many surprises. Sulfur hydride is not an isolated example of conventional high-T C superconductivity at high pressures [4][5][6][7][8][9][10][11][12][13], since a few months later also phosphine (PH 3 ) was observed to superconduct at transition temperatures as high as 100 K at 200 GPa [14]. In this case, experimental and theoretical evidences indicate that superconductivity most likely involves a metastable structure of phosphorus hydride, stabilized by a particular, reproducible experimental condition [15,16].…”
Section: Introductionmentioning
confidence: 99%